A Document Review of Exclusionary Practices in the Context of Australian School Education Policy. Issue 4 (25th March 2019) - Iacono, Teresa; Keeffe, Mary; Kenny, Amanda; McKinstry, Carol
Abstract: Internationally, there is a commitment to inclusive education for students with disability. In Australia, equality of access to mainstream schools is a key policy feature, with educational exclusion of children with disability being unlawful. In this review, the aim was to identify and analyze contemporary documents that point to failures in inclusive policy and legislation in Australia and the state of Victoria by demonstrating educational exclusion of school students with disability. A search of the gray literature was conducted to identify relevant documents from 2010 to 2017. Reference lists of retrieved documents were also searched for other sources. The review included 23 documents and findings demonstrated that the needs of children and families are often not met, with a disconnection evident between inclusive educational policy, legislation, and practices that exclude children with disability from mainstream education. Restrictive practices and gatekeeping act to dissuade families from enrolling children in mainstream education, with many seeking enrolment in special schools. However, concerns with special school practices, such as the use of restrictive interventions have been documented. Parents have resorted to homeschooling, with associated emotional and economic consequences. Tensions between schools and parents were evident, with parents not always having the opportunity to be fully involved in decision‐making processes and planning. The key finding of this review was a clear gap between policy and legislative intentions and practices in schools. Lack of clarity on reasonable adjustments and an underpinning research evidence base to policy results in schools being left to develop their own practices. Strong leadership is needed from principals, and a whole of school commitment, to traverse policy practice gaps that continue to impact on the ability of children with disability to be well‐supported in accessing mainstream schools.